Successful hematopoietic stem cell transplantation for two patients with relapse of intrachromosomal amplification of chromosome 21-positive B-cell precursor acute lymphoblastic leukemia - Harada, Tomoya; Toyoda, Hidemi; Tsuboya, Naoki; Hanaki, Ryo; Amano, Keishiro; Hirayama, Masahiro (Frontiers in Pediatrics, 2022)
In children with relapsed acute lymphoblastic leukemia (ALL), it is essential to identify patients in need of treatment intensification. Minimal residual disease (MRD)-based treatment stratification resulted in excellent survival in children with late relapsed B-cell precursor (BCP)-ALL. Chemotherapy alone produced a favorable outcome in patients with negative MRD after induction. The genetic abnormality also plays an important role in determining the prognosis and stratification for treatment. Intrachromosomal amplification of chromosome 21 (iAMP21) is associated with a poor outcome and a high risk for relapse, and there is no standard treatment after relapse. Herein, we present two patients with relapsed iAMP21-positive ALL who were successfully treated by cord blood transplantation (CBT). Although both patients had late bone marrow relapse and favorable MRD response, CBT was performed due to iAMP21 positive. Patients 1 and 2 have been in remission post-CBT for 15 and 45 months, respectively. Patients with relapsed iAMP21-positive ALL may be considered for stem cell transplantation even in late relapses and favorable MRD response.